Glucagon Like Peptide (Glp – 1) Receptor: A Promising Therapeutic Target for Screening of Herbal Antidiabetic Compounds - Pande Katare, Deepshikha (Asian Journal of Pharmaceutics (AJP), 2018)
Background: Diabetes mellitus and its associated complications have become endemic to developing countries and major threat to health economy of developed nations. Although there are a number of allopathic medicines available for its treatment, they present a lot of challenges due to their adverse effects. Hence, a need for a target-specific herbal alternative is required. Aim: This study explores glucagon-like peptide-1 (GLP-1) protein as a possible therapeutic target for various antidiabetic compounds. Methods: Albino Wistar rats were used as subjects to screen the differentially expressed proteins in type 2 diabetes-induced rats and identify and characterize novel targets for screening of herbal antidiabetic compounds. Widely used and well-established single dose (40 mg/kg) STZ i.p. acute model was used to induce the hyperglycemia. Glucagon-like Peptide-1Receptor was identified in rat’s serum. Plant-based anti-hyperglycemic compounds were docked at various phases of GLP-1 receptor to identify the most potent compound having high antidiabetic efficacy. Results: Ten different herbal compounds were docked against GLP-1 for antidiabetic efficacy using research collaborator for structural bioinformatics - protein data bank. It was found that Myricetin a flavonoid extracted from the leaves of Myrica rubra bonds to the GLP/receptor using least of energy and hence is best of ligand among all available options. Conclusion: Myricetin does have the best of antidiabetic potential out of all 10 screened herbal drugs, as depicted in the docking studies. GLP-1 receptor has shown the promising results as a possible target for antidiabetic drug screening.